Clinicopathological features, surgical treatments, and survival outcomes of patients with small bowel adenocarcinoma. Issue 31 (August 2017) - Zhang, Shuisheng; Yuan, Wei; Zhang, Jianwei; Chen, Yingtai; Zheng, Cuiling; Ma, Jie; Jiang, Qinglong; Zhao, Yajie; Xu, Quan; Wang, Chengfeng
Abstract : Abstract: To date, because of their rarity, the clinicopathological features and surgical outcomes of small bowel adenocarcinomas (SBAs) have been insufficiently explored. We evaluated the clinicopathological features and long-term outcomes of patients who underwent surgery for SBA. This retrospective study (from 1999 to 2016) examined patients with SBA treated surgically at the China National Cancer Center/Cancer Hospital. Clinicopathological features, preoperative evaluation, surgical treatment, and outcome parameters were reviewed and analyzed. Among the 241 patients studied, pancreaticoduodenectomies were performed in 51.0%, partial resection in 24.5%, palliative bypass surgery in 23.7%, and abdominal exploration in 0.8% of the patients. Majority of the patients were diagnosed at an advanced disease stage, and the duodenum was the most common tumor site. Postoperative complications occurred in 44.4% of the patients. Median overall and progression-free survival rates were 22.0 and 13.0 months, respectively. The 5-year overall and progression-free survival rates for patients with duodenal adenocarcinoma were 30.2% and 21.7%, respectively. Duodenal adenocarcinomas, lymph node metastases, distant metastases, poor differentiation, and lymphovascular invasion were associated with poor overall survival outcomes. The 3 factors associated with progression-free survival were the degree of differentiation, lymph node metastases, and distant metastases. Surgery remains the mainstay of treatment for SBA. A poor prognosis could be owing to the site, metastasis, differentiation, and lymphovascular invasion; however, the prognosis may improve through early diagnosis and operation.